2020
DOI: 10.1186/s11658-020-00237-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-361-3p suppresses serotonin-induced proliferation in human pulmonary artery smooth muscle cells by targeting SERT

Abstract: Background Abnormal proliferation of pulmonary artery smooth muscle cells (PASMCs) is a key mechanism in pulmonary arterial hypertension (PAH). Serotonin (5-hydroxytryptamine, 5-HT) can induce abnormal proliferation of PASMCs. The role of miR-361-3p in serotonin-induced abnormal PASMCs proliferation remains unclear. Methods The miR-361-3p level was analyzed in plasma from PAH patients and normal controls and in human PASMCs (hPASMCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…Previous studies have confirmed the downregulation of miR‐224‐5p and miR‐361‐3p in IPH patients. [ 22 , 23 ] Here, we also verified miR‐224‐5p and miR‐361‐3p were downregulated in the lung tissue homogenate of IPH patients (Figure S12d , Supporting Information) and increased in HPAECs and pulmonary arteries of mice treated with SOX17‐associated exosomes (Figure 4d,e ). It is indicating that miR‐224‐5p and miR‐361‐3p were transported to recipient cells by SOX17‐associated exosomes.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have confirmed the downregulation of miR‐224‐5p and miR‐361‐3p in IPH patients. [ 22 , 23 ] Here, we also verified miR‐224‐5p and miR‐361‐3p were downregulated in the lung tissue homogenate of IPH patients (Figure S12d , Supporting Information) and increased in HPAECs and pulmonary arteries of mice treated with SOX17‐associated exosomes (Figure 4d,e ). It is indicating that miR‐224‐5p and miR‐361‐3p were transported to recipient cells by SOX17‐associated exosomes.…”
Section: Resultssupporting
confidence: 70%
“…Then, the functional experiment further verified the inhibiting effect of miR-224-5p and miR-361-3p on the increased activity of caspase 3 induced by serum-free and the increased activity of NFĸB p65 induced by hypoxia and TNF𝛼. The reduced expression of miR-224-5p and miR-361-3p were further confirmed in the lung tissues of IPH patients, which has also been reported in PH-associated [22,23] miR-224-5p and miR-361-3p alone played a protective role under various experimental conditions, and their combined application greatly enhanced this efficiency. It has been demonstrated that the combined application of multiple miRNAs in disease-relevant pathways mediates cancer progression [48,49] and cardiac dysfunction.…”
Section: Discussionsupporting
confidence: 62%
“…SERT is a target for miR-361-3p action, as upregulation of SERT attenuated the effects of decreased miR-361-3p on serotonin induced pulmonary artery smooth muscle cell proliferation. The authors thus concluded that miR-361-3p may be a potential target for PAH therapies [ 73 ].…”
Section: Molecular Pathways In Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Similarly, the 5-HTT inhibitors, fluoxetine and citalopram, impeded human PASMC growth in vitro by blocking SERT expression [ 106 ]. miR-361-3p overexpression suppressed serotonin-induced human PASMC proliferation by lowering SERT levels [ 107 ], indicating that SERT induced PASMC proliferation. Because SERT mediates indolamine uptake in SMCs, the mitogenic effect of 5-HT on PASMCs is ascribed to 5-HT internalization by SERT.…”
Section: The Gut Microbiota and Pulmonary Arterial Hypertensionmentioning
confidence: 99%